Plate load test for multilayer soil system prepared / Amir Abdul Hakim Hanafiah - Hanafiah, Amir Abdul Hakim (1994)
For shallow foundation design, the prediction of actual performance arc normally done by several methods such as ; Method 1 : Method 2 : Method 3 : Actual field load test. Using static bearing capacity Using plate load test (i.e. model foundation test) In this study, plate load test were used to analyse and examine the performance of isolated footing test. Results obtained were examined in term of : the relationship between size of plate and settlement; the prediction of bearing capacity ; and load settlement relationship. From the test results obtained, the settlement of the plate is between 2.08 to 2.50 times more than those computed theoretically for homogeneous soil ( by Boussinesq's method ) and 1.46 times more than those computed theoretically by EgoroVs method for two-layered soil system. The percentage difference in the predicted ultimate bearing capacity between plate load test and those computed by static formula is 5.6 % for homogeneous soil and 8.0 % for two layered soil system.